INDIKASI INFLASI PADA ELASTISITAS HARGA CABAI RAWIT DOMBA DAN CABAI RAWIT HIJAU DI KECAMATAN TAROGONG KALER KABUPATEN GARUT - Herlina, Wita; Risnawati, Hesti; Qothrun Nada, Ilfa; Murweni, Ira (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2024)
The aim of this research is to determine the price elasticity of lamb cayenne peppers and green cayenne peppers as an indication of inflation in staple foods in Tarogong Kaler District, Garut Regency. This research method uses a quantitative descriptive method with an associative approach. Data collection techniques were observation and interviews. Research data was processed using simple linear regression analysis. The results obtained show that both changes in the price of lamb cayenne pepper (R2=0.881) and the price of green cayenne pepper (R2=0.889), can explain changes in the amount of consumer demand for these two commodities or are called elastic (E≤1). This condition explains how the increase in the price of cayenne pepper can be used as an indicator of inflation which can influence a decrease in the amount of public consumption and reduce the income level of chili traders and producers (farmers) so that local governments need to be aware of the increase in chili prices so that it does not have an impact on increasing inflation.